Basic Sanitation Management at Ibnu Cholil Islamic Boarding School in Bangkalan Regency - Rosalia Tri Oktaviana; Pratiwi Hermiyanti; Rachmaniyah Rachmaniyah; Hadi Suryono; Yuli Tri Suhartiwi; Seow Ta Wee (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Basic sanitation is critical to achieving health as it plays a major role in preventing the spread of disease. The benefits of basic sanitation management include the prevention of diseases such as diarrhea, dengue, and typhoid. The purpose of this study was to determine the management of basic sanitation which includes the provision of clean water, waste management, provision of healthy latrines, and provision of sewerage in Ibn Cholil Islamic Boarding School, Bangkalan Regency. The type of research used is descriptive with a qualitative approach. Research instruments were interviews and observation checklists with POAC assessment criteria (planning, organizing, actuanting, and controlling). The research variables were the provision of clean water, waste management, provision of healthy latrines, provision of sewerage. The results of the research on basic sanitation management of clean water supply in male dormitories (71%) are in the good category and in female dormitories (62%) are in the sufficient category. Waste management in male dormitories (52%) and in female dormitories (56%) is included in the sufficient category. The provision of healthy latrines in male dormitories (68%) and in female dormitories (73%) is categorized as good. The condition of sewerage in male dormitories (10%) and in female dormitories (24%) is categorized as insufficient. The conclusion of this study shows that the implementation of basic sanitation management management in Ibn Cholil Islamic boarding school, Bangkalan Regency is in the moderate category. It is necessary to educate about basic sanitation management and direct monitoring from the health center. INDEX TERMS Basic Sanitation, Management, Boarding School.